2021
DOI: 10.1108/ijppm-05-2020-0246
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the interrelationship among job resources, job demands, work and organizational engagement

Abstract: PurposeThis study aims to test the hypothesized moderated mediation process combining job resources, job demands, work engagement, job satisfaction and organizational engagement, which proposes that work engagement can be considered as a mediator between the relationship of job resources with job satisfaction and organizational engagement, and such mediation effect is moderated by level of job demand.Design/methodology/approachData were collected from Junior Management Grade–Scale I officers of 442 branches of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…The narrative review of 40 studies conducted by Saks et al, (2022) allows us to conclude that work engagement scores tend to be higher than organisational engagement. The results of our study support these claims and we tend to agree with the authors (Tenerife and Galingan, 2018;Rai and Maheshwari, 2020;Saks et al, 2022;Rai and Chawla, 2022) who propose work engagement as a predecessor of organisational engagement. Furthermore, our research showed that, across all generations, work engagement positively affects organisational engagement.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The narrative review of 40 studies conducted by Saks et al, (2022) allows us to conclude that work engagement scores tend to be higher than organisational engagement. The results of our study support these claims and we tend to agree with the authors (Tenerife and Galingan, 2018;Rai and Maheshwari, 2020;Saks et al, 2022;Rai and Chawla, 2022) who propose work engagement as a predecessor of organisational engagement. Furthermore, our research showed that, across all generations, work engagement positively affects organisational engagement.…”
Section: Discussionsupporting
confidence: 93%
“…Rai and Maheshwari (2020) propose work engagement as a predecessor of organisational engagement that implies that the organisation needs to achieve work engagement first to realise the benefit of organisational engagement, which according to Saks et al (2022), is important if not more important than work engagement. Later research by Rai and Chawla (2022) further strengthened the notion that organisational engagement is a consequence of work engagement.…”
Section: Link Between Work Engagement and Organisational Engagementmentioning
confidence: 98%
“…The Job Demands-Resources (JD-R) framework appears to be popular among contemporary researchers studying engagement (Albrecht et al, 2018;Mayuran & Kailasapathy, 2022;Rai & Chawla, 2021;Rai & Maheshwari, 2020). For instance, Rai and Chawla (2021) base their model for investigating the relationships between job demands, resources, engagement and satisfaction on the JD-R framework. However, JD-R framework has been criticized for neglecting heterogeneous contextual factors pertaining to engagement (Bailey et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, employees will more likely display positive attitudes toward the organization (Han et al, 2020). Literature has suggested a positive effect of job engagement on job satisfaction across varied business contexts, such as Belgian medical clinics (Côt e et al, 2021) and public sector banks in India (Rai and Chawla, 2022). Thus, the following hypothesis can be proposed: H4.…”
Section: Job Engagement and Job Satisfactionmentioning
confidence: 98%